Mycorrhizal association and its relation with pteridophytes - Kumari, Pratibha; Bhatia, Meenam; Giri, Priti; Uniyal, Prem Lal (Frontiers in Microbiology, 2024)
Mycorrhizal association is one of the earliest and diversely distributed symbiotic associations on the Earth. This association helped early terrestrial plants to colonize the land by improved supply of nutrients like phosphate, nitrogen and zinc. It also helped plants to tolerate unfavorable soil conditions with increased water retention capacity, resistance to drought and pathogens. In return, fungi benefitted with carbon as their food source from the plants. More than 80% of terrestrial plants including pteridophytes, gymnosperms and angiosperms are reported to form arbuscular mycorrhizal (AM) association. Plants with root systems appeared on land during the Devonian period and many of them like pteridophytes still exist today. Various molecular and fossil studies confirm that the plants belonging to Ordovician-Devonian are associated with fungi, which are very similar to genus Glomus. AM association is very common in pteridophytes and the growth of its sporophyte and gametophyte is directly affected in the presence of AM association. Pteridophytes as early land plants with root systems have a very significant place in the plant kingdom. They have evolved and adapted to fill various habitats and facilitated early terrestrialization of other land plants by providing suitable niche with the help of AM fungi. In spite of pteridophytes being a very important plant group in the land system, very few reports are available on fungal-pteridophyte association. The present review is an effort to gather information about AM association in pteridophytes that might help in unraveling the evolution and significance of plant and fungi association.